RANCANG BANGUN PRESENSI KARYAWAN BERBASIS NFC STUDI KASUS UNIVERSITAS PGRI WIRANEGARA - Dimas Rega Hadiatullah (Universitas Nusa Cendana, 2023)
There are many indications that show the performance of an employee, one of which is presence or attendance at work. In the institution of Universitas PGRI Wiranegara or UNIWARA, the employee attendance system still uses a manual system or is not modern. In the era of the COVID-19 pandemic, an attendance system based on no physical contact is the best choice. This study aims to develop an automatic attendance system without physical contact using Near Field Communication (NFC). NFC is a wireless computer network technology that uses radio frequency that allows you to connect without physical contact combined with applications developed using the SDLC (Software Development Life Cycle) method that can process data automatically. The final results of the study show that, from the tests carried out by this application, it makes it easy to make attendance without physical contact, where previously physical contact was still used. And in testing using Blackbox there were no errors, whereas when testing an objective system to respondents it was found that this system is easy to use, useful for users, has an attractive appearance, and is easy to understand.